SOIL ENZYME ACTIVITY, SOIL MICROBIAL COMMUNITIES, MICROBIAL BIOMASS CARBON CHANGES AND SEED COTTON YIELD UNDER DIFFERENT NUTRIENT MANAGEMENT PRACTICES IN Bt COTTON - M. RANJITH; S. SRIDEVI; M.VENKATA RAMANA; P.CHANDRASEKHAR RAO (The Bioscan, 2015)
Nutrient supply and availability during crop growth influences various microbial mediated biochemical reactions and nutrient transformations. Studies were conducted on a sandy clay loam during kharif, 2013-14 to understand the effect of different fertilizer doses on soil microbial activity and yield of Bt cotton. Dehydrogenase activity, a key biochemical indicator, was higher under soil test based fertilizer application with 3.43 μg of TPF g -1 day -1 . Farmers’ practice of excessive fertilizer application had negative impact on DHA (2.57 μg TPF g -1 day -1 ). Urease activity decreased by 24 to 27% with 150% RDF with and without sulphur @ 30 kg ha -1 when compared to 100% RDF. Increasing fertilizers from 100 to 150% caused inhibitory effect on the activity of acid and alkaline phosphatases. Soil microbial population and microbial biomass carbon did not show significant variations with treatments. Although higher seed cotton yield of 3847 kg ha -1 was realized by increasing fertilizer dose to 150%, it was on par with the yield realized in 100% NPK (3616 kg ha -1 ) and soil test based fertilizer application (3688 kg ha -1 ). Farmers’ practice of application of very high doses of fertilizers resulted in slightly lower yield (3582 kg ha -1 ) than 100% RDF.